The transformation of intimacy: mate selection in a Ghanaian municipality - Odoi, E.Y. (Ghana Social Science Journal, 2018)
Mate selection is a sine qua non for marriage. Generally, studies on mate selection have focused on attributes that individual’s desire in a potential mate and how gender influences these preferences without describing the processes of mate selection. To fill this gap, this paper highlights the processes of mate selection and how social variables such as place of residence, education and gender influence the mate selection standards of individuals. It also highlights the sources of these standards and how they might have changed overtime. Employing a mixed-method approach and grounded in the social role theory, the study points to two main findings: first at different stages of their lives, individuals get involved in different ‘romantic’ relationships before finally settling down with a particular partner. The study also shows that most individuals have a preconceived set of mate selection standards prior to the selection of a partner
Ghana Social Science Journal, 15(1)
Keywords: Preferences; Ideal Mate; Assortative Mating; Gender; Education; Place of Residence